Raman spectroscopy for the determination of hydrogen concentration in liquid organic hydrogen carrier systems - Jander, Julius Hans; Chittem, Pranay Kumar; Kerscher, Manuel; Rausch, Michael Heinrich; Wasserscheid, Peter; Fröba, Andreas Paul (International Journal of Hydrogen Energy, 2024)
This work reports on the development of a calibration approach of Raman spectroscopy for the determination of the concentration of dissolved hydrogen (H2) in representative compounds and mixtures of liquid organic hydrogen carrier (LOHC) systems based on diphenylmethane and ortho-benzyltoluene (o-BT). Hydrogen solubility data are measured by the isochoric-saturation method at temperatures and pressures up to 473 K and 7 MPa where Raman spectra of the saturated liquid phase are recorded in parallel. By selecting an appropriate frequency range attributed to the LOHC signatures in isotropic spectra, a calibration which is independent of the LOHC system, the degree of hydrogenation of the LOHC samples, and temperature can be found. The transfer of the calibration to another setup is successfully tested up to 523 K and 6 MPa, where H2 solubilities in the fully hydrogenated o-BT can be determined with an average absolute deviation of 0.009 from theoretically calculated data.
CRIS-Team Scopus Importer:2024-06-21
Keywords: Benzyltoluene; Density; Diphenylmethane; Hydrogen solubility; Isochoric-saturation method; Polarization-difference Raman spectroscopy